1997
DOI: 10.1002/(sici)1097-0231(19971015)11:15<1709::aid-rcm5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-mass spectrometry analysis of dehydrogenation lignin polymers with various syringyl/guaiacyl ratios

Abstract: The present paper describes the application of pyrolysis-mass spectrometry (PYMS) to the analyses of lignocellulosic materials. Dehydrogenation lignin polymers (DHPs) with various syringyl/guaiacyl (S/G) ratios, and a standard, milled wood lignin from Aesculus turbinata Blume, were pyrolyzed at 500°C for 4 s and the volatile products were ionized by low-voltage (20 eV) electron impact. The PYMS spectra of the lignins are shown with identification of most mass peaks. Of the observed mass peaks, the intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
(33 reference statements)
0
27
1
Order By: Relevance
“…It was presumed that as the decomposition of pectin was complete at a low temperature, the generation of other products at higher temperatures hindered the formation of alcohols. The fraction of acids, composed mainly of acetic acid, was highest at 500 o C. In contrast, the yield of phenols, the main products of decomposition of lignin [27], increased with increasing temperature. The yields of ketones and furan derivatives also increased with increasing pyrolysis temperature.…”
Section: Py-gc/msmentioning
confidence: 92%
See 1 more Smart Citation
“…It was presumed that as the decomposition of pectin was complete at a low temperature, the generation of other products at higher temperatures hindered the formation of alcohols. The fraction of acids, composed mainly of acetic acid, was highest at 500 o C. In contrast, the yield of phenols, the main products of decomposition of lignin [27], increased with increasing temperature. The yields of ketones and furan derivatives also increased with increasing pyrolysis temperature.…”
Section: Py-gc/msmentioning
confidence: 92%
“…From our results, the pyrolysis products were in good accordance with the main composition of mandarin peel, i.e., pectin, hemi-cellulose, lignin and cellulose. It was recently reported that acetic acid was mainly formed from hemicellulose [25]; whereas, levoglucosan was from cellulose [26], phenols from lignin [27], and furfural and 1-hydroxy-propanone from holocellulose [28]. Zhou et al [24] studied the formation mechanism of the pyrolysis gases released during the pyrolysis of pectin under conditions that simulated a cigarette smoldering.…”
Section: Py-gc/msmentioning
confidence: 99%
“…3a; column five of Table 4). The spectra are somewhat visually similar to spectra of aspen wood and lignin obtained by using Py-molecular-beam sampling MS [48]; spectra of beech wood obtained by using temperature-programmed Py-field ionization MS [49]; spectra of cottonwood lignin obtained by using temperature-programmed in-source Py-MS [50]; and spectra of Aesculus turbinata lignin obtained by using in-source Py-MS [51]. However, upon close inspection, there are more differences than similarities between the DART-MS spectra and those obtained by using Py-MS.…”
Section: Hardwood Bleached Chemithermomechanical Pulp (Hw-bctmp)mentioning
confidence: 99%
“…Its molecular ion counterpart with m/z 400 may be seen clearly in in-source Py-MS spectra obtained from wood of Calluna vulgaris and Aesculus turbinata [51,53] and from an organosolv lignin [54]. The structure suggested in Table 4 for this ion is that of an oxidized dimethoxy analog of 3,4-divanillyltetrahydrofuran (shonanin), which is a natural lignan whose syringyl analogs have been found in emissions from the combustion of both hardwoods and softwoods [55].…”
Section: Hardwood Bleached Chemithermomechanical Pulp (Hw-bctmp)mentioning
confidence: 99%
“…Mann et al studied the variation in the S:G ratio of lignin in switchgrass grown in different conditions by comparing pyrolysis product mass intensities of certain sinapyl marker compounds to coniferyl markers [4]. Izumi and Kuroda used Py-MS spectra of lignin model polymers to correlate marker ion mass intensity S:G ratios to the molar S:G ratios in the synthesized polymers [30]. Recently, Asmadi et al [31] pyrolyzed mixtures of syringol and guaiacol in order to understand the reactivities of the aromatic nuclei in hardwood lignins.…”
Section: Introductionmentioning
confidence: 99%